ANALISIS PENGGUNAAN ISTIHSAN DALAM TRANSAKSI JUAL BELI VIA VENDING MACHINE - Salimadin Salimadin (JURNAL PROFIT, 2020)
Method used by the scholars, especially among Hanafiyah, not separated from it, with the rapid development of science and technology istihsan was born as a solution in the determination of new laws that do not yet have provisions both in the text of Istihsan is a determination method of Islamic law based on the principle of Qur’an and Hadith and based on Islamic Shari'a purpose. istihsan itself to apply a the Qur'an and Hadith, as for new cases that require answers to the determination of the law including in the field of muamalah such as buying and selling online and shopping in supermarkets. In contemporary finance and economics such cases require legal settlement, the istihsan here is present and serves as a solution to the settlement of the law in permissibility or not a transaction contract based on tradition of modern humans.